Midterm Review of the Caribbean Regional Technical Assistance Centre (CARTAC). (Policy Papers; Policy Paper, 2003)
The mid-term review was undertaken to help funding and implementing agencies foster a greater level of understanding of the Caribbean Regional Technical Assistance Center's (CARTAC) work. It ascertains activities to date and should help the Steering Committee determine optimal strategies for the Center's continuation.